Ideological differences in attitude and belief similarity: distinguishing perception and reality. Issue 1 (1st January 2020) - Stern, Chadly
ABSTRACT: Attitude and belief similarity have long stood as topics of inquiry for social psychology. Recent research suggests that there might be meaningful differences across people in the extent to which they perceive and actually share others' attitudes and beliefs. I outline research examining the relationship between political ideology and the perception and reality of attitude similarity. Specifically, I review research documenting that (a) conservatives perceive greater ingroup similarity than do liberals, (b) conservatives overestimate and liberals underestimate ingroup similarity, (c) liberals and conservatives both underestimate similarity to outgroup members, and (d) liberals possess more actual ingroup similarity than do conservatives on a national level. Collectively, this review contributes to understanding how political ideology relates to (perceived) attitude similarity.